(untitled) (Applied Biological Research, 2017)
Rodenticides are the preferred option to prevent rodent attacks to crop produce. However, secondary poisoning and development of shyness and resistance among rodents after exposure to toxic chemicals has increased the search for plant based effective, safe and ecofriendly control methods. In present study, repellent and feeding behaviour of house rat in response to 0.4% cinnamamide based formulation was studied using automated Ethovision video tracking system and feed scale consumption monitor. Results revealed absence of primary repellent effect of cinnamamide formulation but existence of its secondary repellent effect against house rat. Repellent effect of cinnamamide increased with time during treatment period. Moreover, during treatment period, rats handled treated bait less frequently as compared to the untreated bait because feeding bouts events and feeding bout time also decreased during treatment period.